Niche Sociality: Approaching Adversity in Everyday Life. (February 2023) - Manning, Nick; Birk, Rasmus; Rose, Nikolas
How should sociologists understand the everyday lives of those living in adversity, coping with the experience of structural violence? In this article, focusing on the urban experience, we suggest a perspective on 'everyday life' that can encompass corporeal, mental, relational and social dimensions, which we term 'niche sociality'. First, we use Gibson's niches and affordances to enrich the post-representationalist understanding of human beings as embodied/cultural/environmentally embedded organisms. Second, we enrich Gibson's niches and affordances with theories for 'small-scale' sociality drawn from social practice theory and interaction ritual chains. Third, we illustrate the productivity of these ideas throughout the article, by grounding our conceptual work in empirical examples that analyse the everyday lives and mental life of migrant workers in Shanghai. Niche sociality, we argue, is a way of framing the experience of the everyday, a perspective that could – perhaps should – provoke novel ecosocial studies of adversity.